NaProGraph: Network Analyzer for Interactions between Nucleic Acids and Proteins - Nematzadeh, Sajjad; Aydin, Nizamettin; Kurt, Zeyneb; Torkamanian-Afshar, Mahsa (Current Bioinformatics, 2024)
Background: Interactions of RNA and DNA with proteins are crucial for elucidating intracellular processes in living organisms, diagnosing disorders, designing aptamer drugs, and other applications. Therefore, investigating the relationships between these macromolecules is essential to life science research. Methods: This study proposes an online network provider tool (NaProGraph) that offers an intuitive and user-friendly interface for studying interactions between nucleic acids (NA) and proteins. NaPro- Graph utilizes a comprehensive and curated dataset encompassing nearly all interacting macromolecules in the Research Collaboratory for Structural Bioinformatics (RCSB) Protein Data Bank (PDB). Results: Researchers can employ this online tool to focus on a specific portion of the PDB, investigate its associated relationships, and visualize and extract pertinent information. This tool provides insights into the frequency of atoms and residues between proteins and nucleic acids (NAs) and the similarity of the macromolecules' primary structures. Conclusion: Furthermore, the functional similarity of proteins can be inferred using protein families and clans from Pfam.
Keywords: NA protein